2022
DOI: 10.3389/fpls.2022.1022935
|View full text |Cite
|
Sign up to set email alerts
|

Comparative physiological and soil microbial community structural analysis revealed that selenium alleviates cadmium stress in Perilla frutescens

Abstract: Cadmium (Cd) toxicity not only affects plant growth and development, but also affects human health through the food chain. Several studies have demonstrated that Selenium (Se) alleviates Cd stress in plants; however, whether and how Se-alleviated Cd stress by regulating the structure of soil microbial community remain largely unclear. Here, we investigated the alleviating effects of exogenous applied Se (foliar spraying or root application) on plant growth under Cd stress in perilla (Perilla frutescens L.) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Studies have shown that treatment with Se alters the structural composition of soil microbial communities but does not have a significant impact on the diversity of soil bacterial microbial communities. Proteobacteria and Bacteroidetes decreased under Cd toxicity, whereas they increased after applying Se in [38], which is consistent with the results of this study. Proteobacteria and Bacteroidetes are involved in the degradation of organic matter and the biotransformation of mineral elements and play a role in the degradation of macromolecular organic matter in soil.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that treatment with Se alters the structural composition of soil microbial communities but does not have a significant impact on the diversity of soil bacterial microbial communities. Proteobacteria and Bacteroidetes decreased under Cd toxicity, whereas they increased after applying Se in [38], which is consistent with the results of this study. Proteobacteria and Bacteroidetes are involved in the degradation of organic matter and the biotransformation of mineral elements and play a role in the degradation of macromolecular organic matter in soil.…”
Section: Discussionsupporting
confidence: 92%
“…The relative abundance of Sphingomonas was positively correlated with L-proline, hydroxyisocaproic acid, xanthine, pantothenic acid and L-arginine (P < 0.05). Sphingomonas had extensive metabolic capacity for aromatic compounds and could promote the production of many metabolites [51] . The relative abundance of Bacillus was positively correlated with the content of inosine (P < 0.05).…”
Section: Correlation Analysis Between Microorganisms and Differential...mentioning
confidence: 99%
“…The common inorganic Se is mainly elemental Se (Se 0 ), selenide (Se 2− ), selenite (Se 4+ ), and selenate (Se 6+ ); organic Se is mainly represented by selenocysteine and selenomethionine [4]. In recent years, studies on inorganic Se have been reported in many aspects, such as the effects of Se on crop growth and absorption [5,6], the interaction between Se and metals on plants or soils [7][8][9], and the morphology and transformation of Se in the soil [10]. To date, the application of inorganic Se (selenite and selenate) to the soil as Se fertilizer has become the norm [11].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [20] found that selenite would be transformed into a stable and low-toxicity state in the soil, increase persistent free radicals, and thus reduce the abundance and diversity of microorganisms. Yang et al [7] showed that root application of Se could increase the bacterial abundance in cadmium-contaminated soil and improve the soil microbial community structure. Cheng et al [21] showed in a pot experiment of rapeseed that Se application could contribute to the enrichment of beneficial rhizosphere microorganisms in rapeseed rhizosphere soil, thus promoting plant growth.…”
Section: Introductionmentioning
confidence: 99%